A Roadmap to Uranium Ionic Liquids: Anti‐Crystal Engineering. Issue 21 (15th April 2014) - Yaprak, Damla; Spielberg, Eike T.; Bäcker, Tobias; Richter, Mark; Mallick, Bert; Klein, Axel; Mudring, Anja‐Verena
Abstract In the search for uranium‐based ionic liquids, tris(N, N‐dialkyldithiocarbamato)uranylates have been synthesized as salts of the 1‐butyl‐3‐methylimidazolium (C4mim) cation. As dithiocarbamate ligands binding to the UO22+ unit, tetra‐, penta‐, hexa‐, and heptamethylenedithiocarbamates, N, N‐diethyldithiocarbamate, N‐methyl‐N‐propyldithiocarbamate, N‐ethyl‐N‐propyldithiocarbamate, and N‐methyl‐N‐butyldithiocarbamate have been explored. X‐ray single‐crystal diffraction allowed unambiguous structural characterization of all compounds except N‐methyl‐N‐butyldithiocarbamate, which is obtained as a glassy material only. In addition, powder X‐ray diffraction as well as vibrational and UV/Vis spectroscopy, supported by computational methods, were used to characterize the products. Differential scanning calorimetry was employed to investigate the phase‐transition behavior depending on the N, N‐dialkyldithiocarbamato ligand with the aim to establish structure–property relationships regarding the ionic liquid formation capability. Compounds with the least symmetric N, N‐dialkyldithiocarbamato ligand and hence the least symmetric anions, tris(N‐methyl‐N‐propyldithiocarbamato)uranylate, tris(N‐ethyl‐N‐propyldithiocarbamato)uranylate, and tris(N‐methyl‐N‐butyldithiocarbamato)uranylate, lead to the formation of (room‐temperature) ionic liquids, which confirms that low‐symmetry ions are indeed suitable to suppress crystallization. These materials combine low melting points, stable complex formation, and hydrophobicity and are therefore excellent candidates for nuclear fuel purification and recovery.